The role and regulatory mechanism of lysosome associated protein transmembrane 4β in tumors - Yang, Yuteng; Li, Yumei; Wang, Yaqi; Chen, Xi; Yao, Yisong; Li, Dongxian; Yu, Guohua; Song, Xicheng (Frontiers in Oncology, 2025)
The oncogene LAPTM4B (encoding lysosome-associated protein transmembrane-4β), first cloned in hepatocellular carcinoma cells, is located on chromosome 8q22.1 and encodes two isoforms, LAPTM4B-35 and LAPTM4B-24. LAPTM4B proteins have four transmembrane structural domains and are mainly distributed in lysosomal and endosomal membranes of cells. Studies have shown that LAPTM4B is overexpressed in a variety of cancers, in which the genetic polymorphism of LAPTM4B is associated with tumor susceptibility. LAPTM4B also regulates various cell signaling pathways, interacts with autophagy-related proteins and ceramides, and regulates the autophagy process and the release of exosomes, which in turn affect the survival and drug resistance of tumor cells. In conclusion, this paper summarizes recent research on LAPTM4B, aiming to explore the role and potential mechanisms of LAPTM4B in a variety of tumors.